How General Practitioners and Their Patients Adhere to Osteoporosis Management: A Follow-Up Survey among Czech General Practitioners - Vytrisalova, Magda; Touskova, Tereza; Fuksa, Leos; Karascak, Roman; Palicka, Vladimir; Byma, Svatopluk; Stepan, Jan (Frontiers in Pharmacology, 2017)
Introduction: General practitioners (GPs) are key participants in osteoporosis (OP) management. The aim was to evaluate their adherence to lege artis management of the disease, potential barriers, and to discuss differences observed in comparison with the baseline survey carried out in 2007; the focus was on secondary prevention. Methods: On behalf of two professional associations, 2-round postal survey among randomly selected GPs (>1/4 of all Czech GPs) was performed in 2014. The questionnaire covered areas concerning GP´s role in the fight against OP, knowledge about OP, management of OP-related fractures, barriers to the management of OP, system- and patient-related in particular, and availability and use of information sources. Results: The overall questionnaire return rate was 37% (551 respondents); mean age of the respondents was 53y (37% men). The GP's role in the treatment of OP was rated as essential in 28% and 37% of men and women, respectively (P = 0.012). The guideline for diagnosis and treatment of OP for GPs was considered accessible by 92% of respondents. As much as 60% of the respondents were adherent to the guideline, i.e. used it repeatedly. The knowledge of several risk factors was very good, however, recommended daily intake of calcium was stated correctly by only 41% of respondents, and daily intake of vitamin D by only 40%. Three quarters reported active steps after a fracture: referral to a specialist, life-style recommendations, prescription of calcium/vitamin D supplements. Half of the respondents focus on fall prevention. System-related barriers such as lack of possibility to prescribe selected drugs (61%) and financial limits set by health insurance company (44%) were most frequently reported. Patient-related barriers were also common, patient´s non-adherence (reported by 29%) and patient´s reluctance to go to a specialist (18%). Conclusion: GPs adhered to OP management more than in 2007. Knowledge of risk factors and involvement in post-fracture care was relatively high. Compared to baseline survey, patient-related barriers, patient non-adherence in particular, were more common. Prescribing conditions are still an important issue. Among GPs, education should be focused on calcium and vitamin D intake, doses, sources, and supplements.